The Influence of Channa Striata Extract Emulgel on Incision Wound Healing in White Rats - Lucia Hendriati; Suryo Kuncorojakti; Teguh Widodo; Heny Kristi Meitasari; Wilis Prasasti (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Snakehead fish (Channa striata) have high albumin content, a protein needed for cell development and the formation of new tissue. The aim of this study was to determine the influence of snakehead fish extract emulgel given topically on incision wounds in white rats. The parameters of wound healing consist of wound length, a number of neutrophils, macrophages, fibroblasts and density of collagen. The white rats divide into three groups of (n = 6), one group was given the emulgel base as the negative control, one group of povidone-iodine as the positive control, and one group of snakehead fish extract 10% emulgel. White rats were sacrificed on the third and seventh days for microscopic observations. The results showed that snakehead fish extract emulgel can accelerate incision wound healing: decrease wound length, increase the number of neutrophil and macrophages cells, increase the average number of fibroblasts and increase collagen density on white rats.